Old Library Manuscript Catalogues in Martynas Mažvydas National Library of Lithuania - Steponaitienė, Jolita (Bibliotheca Lituana, 2012)
Library catalogue or inventory book is one of the most important sources for exploring its stock development, collection creation strategy, content of documents. Catalogue contains a lot of information about content of collections, quality and quantity aspects, and enables reconstruction of libraries which had been closed, dispersed or damaged by various disasters. Catalogues of old, especially non-operating libraries can also play role of reflections of scientific, cultural, social life of certain historical period, sometimes even of witnesses of the whole epoch. This historical source is very important for history of book and library. Their analysis can fill gaps in research of cultural communication of certain periods. Library catalogue is an information search system giving better orientation in the library to the reader, satisfaction of his informational needs and expectations. Exploring of library catalogue can be multiform depending on the subject and object of the exploration. Scientific researches of library catalogues are not popular; they are rather additional source of book history. The old catalogues give possibility to reconstruct traditions and culture of forming catalogues of that time, retrieve regulations and specifics of their forming. The article reveals content of catalogues of institutional, personal libraries of 19th-20th centuries preserved in the Rare Book and Manuscript Department of Martynas Mažvydas National Library of Lithuania, their provenance attributes and physical features, making emphasis on Lithuanian books in these libraries. These are catalogues or lists of books owned of Samogitian Seminary, Ateitininkai Chapter established by Lithuanians who moved to Voronezh (Russia) during the 1st World War, The Januškevičiai (progenitors of the Dobužinskiai family), explorer of Lithuanian language Kazimieras Jaunius. These catalogues were selected from library catalogues of the National Library, because the institutions and persons mentioned were important for Lithuanian history and culture. Old library catalogues present evidence what important sources they can be for exploring of various historical stages of the country, historical and cultural heritage of various institutions, organizations or personalities, cultural and informational communication, distribution of a certain book, its popularity in libraries of various levels, culture and traditions of library catalogues forming during the certain time period.